Value of Wilms tumor gene product (WT-1) immunohistochemical expression in ovarian neoplasms - Abd El hafez, Amal; E l-dosoki, Ibrahim; Sirag, Soheir; Gado, Asmaa; Denewer, Adel (International Journal of Medicine, 2014)
Background: Ovarian cancer is a fatal malignancy among females worldwide. The wide morphologic variation among ovarian neoplasms poses diagnostic difficulties. Wilms' tumor gene protein (WT-1) is a recently added marker to the diagnostic panel of ovarian neoplasms and may have prognostic implications. Objective: To evaluate the immunohistochemical expression of WT-1 protein in a broad array of ovarian neoplasms including metastases, identify its value in diagnosis and find out its association with the histopathological parameters including histological subtype, grade and FIGO stage. Materials and methods: This retrospective study was conducted on 93 ovarian neoplasms collected from Pathology Department, Mansoura University and Mansoura Oncology Center. Immunohistochemistry was performed for WT-1 protein using the avidin-biotin-peroxidase technique. Nuclear staining of tumor cells was considered as positive. Statistical analysis was performed using SPSS version 16.0. Results: Significant statistical difference in WT-1 expression was observed among histological types of ovarian neoplasms (p=0.04) being detected in 90% of serous tumors, in which significant statistical association was found between WT-1expression and grade (p=0.025), but not with stage. Most non-serous carcinomas were WT-1 negative. WT-1 reactivity was observed in tumors with Sertoli cell differentiation but undetectable in all other sex cord, germ cell, mixed germ cell-sex cord or metastatic tumors. Conclusions: WT-1 is a highly specific marker for ovarian serous carcinomas versus other histological subtypes of ovarian neoplasms including metastases. It should be included in the immunohistochemical workup of carcinoma of unknown primary in women or in a panel to verify Sertoli cell differentiation in sex cord-stromal tumors.   Keywords: Immunohistochemistry, Ovarian Neoplasms, Serous Carcinoma, Sex-Cord, WT-1.